Clusterin induced by N,N′-Dinitrosopiperazine is involved in nasopharyngeal carcinoma metastasis - Li, Yuejin (Oncotarget, 2015)
Nasopharyngeal carcinoma (NPC) has a high metastatic clinicopathological feature. As a carcinogen factor, N,N′-Dinitrosopiperazine (DNP) is involved in NPC metastasis, but its precise mechanism has not been fully elucidated. Herein, we showed that DNP promotes NPC metastasis through up-regulating anterior clusterin (CLU). DNP was found to increase CLU, matrix metalloproteinases (MMP) 9 and vascular endothelial growth factor (VEGF) expression and activity, further DNP-increased MMP-9 and VEGF expression was through up-regulating CLU. We also found that DNP increased the binding of CLU with MMP-9 or VEGF. DNP induced the motility and invasion of NPC cell, which was inhibited by siRNA-CLU. The clinical investigation showed that CLU, MMP-9 and VEGF were positively correlated with the tumor-node -metastasis (TNM) classification. These results indicate that DNP may promote NPC tumor metastasis through up-regulating CLU, MMP-9 and VEGF expression. Therefore, DNP-increased CLU expression may be an important factor of NPC-high metastasis, and CLU may serve as a biomarker for NPC metastasis.